ATAXIA AND EPILEPSY DUE TO A RARE AUTOSOMAL MITOCHONDRIAL DISEASE. Issue 11 (9th October 2013) - Cheripelli, Bharath Kumar; Duncan, Callum
Abstract : We report a case of a twenty three year old female presenting with status epilepticus due to a rare mutation in a nuclear gene causing mitochondrial dysfunction. She had previously been investigated for an inherited ataxia without a definitive diagnosis being made. She presented as an emergency with focal seizures that rapidly evolved into intractable status epilepticus. Despite prolonged, aggressive treatment in Intensive Care Unit, she remained encephalopathic with persisting seizures. Her younger sister who also has milder symptoms with ataxia visited our hospital on the day of acute admission and revealed some useful information that led us investigate and confirm the diagnosis in our patient. Her younger sister who was a medical student told us that she had been investigated elsewhere and was confirmed to have an autosomal recessive mutation in a nuclear gene named POLG. We tested and confirmed the same POLG mutation in our patient. POLG is a nuclear gene located on long arm of chromosome 15 that encodes the catalytic subunit of mitochondrial DNA polymerase gamma. The defects in this enzyme are associated with disorders of mitochondrial DNA maintenance. POLG mutation has several phenotypes with onset between early childhood to late adulthood. Typical clinical features include ataxia, neuropathy, epilepsy, ophthalmoplegia, myopathy and in some cases liver failure. Liver failure has been associated with treatment with Sodium valproate and this should be avoided in these patients. Prognosis is poor in the presence of epilepsy with mortality rates to be reported to be nearly 80%. After extensive discussions with the family, local ethics team, and medical director, our patient was palliated in the local palliative care hospital where she died peacefully. A clinical intuition is needed for referring these patients to genetic testing and the diagnosis is crucial to inform us the prognosis. We discuss her presentation, management and our patient's phenotype Mitochondrial Spino–Cerebellar Ataxia and Epilepsy (MSCAE).